Processes of building trust in organizations: internal communication, management, and recruiting - Gian Luca Gara; José María La Porte (Church, Communication and Culture, 2020)
The article explores ways to build trust in a very specific area of internal and external communication: recruitment. At first it explores the links that communication and vulnerability have with the sciences that study the human dimension of organizations. Second, it addresses the functional and personal dimension of processes in relation to the forces of order or dispersion that press every organization on a personal or structural level (centripetal and centrifugal force). Trust presents itself as the ring that unites and harmonizes the creative or destructive power of those forces. It is an essential element that makes it possible to manage the vulnerability of organizations and their limitations on an organizational or human level. The hypothesis being made is that recruitment is an essential element of internal and external communication and has a strategic importance for the future of the organization because the mobility of the labor market, contractual conditions, and reduced turnover times require creating an environment of trust and transparency in a short time. This begins with the selection process and develops throughout the future professional projection of workers within the company.